2023
DOI: 10.1021/acsnano.2c11894
|View full text |Cite
|
Sign up to set email alerts
|

Heme-Dependent Supramolecular Nanocatalysts: A Review

Abstract: Enzymes fold into three-dimensional structures to distribute amino acid residues for catalysis, which inspired the supramolecular approach to construct enzyme-mimicking catalysts. A key concern in the development of supramolecular strategies is the ability to confine and orient functional groups to form enzyme-like active sites in artificial materials. This review introduces the design principles and construction of supramolecular nanomaterials exhibiting catalytic functions of heme-dependent enzymes, a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 129 publications
0
6
0
Order By: Relevance
“…To further evaluate the working principle of this system, we measured UV–vis spectra of Target-12/hemin, before and after strand displacement (Figure S26). Both spectra exhibited a peak at 398 nm along with a shoulder at 370 nm, indicating the coexistence of monomeric hemin and μ-oxo bihemin (the dimer of hemin). , Of note, after multiple cycles of the strand displacement reactions, the spectra remained similar. We then investigated the UV–vis spectra in the presence of K 10 , which also exhibited the peak at 398 nm and shoulder at 370 nm (Figure S27).…”
Section: Resultsmentioning
confidence: 90%
“…To further evaluate the working principle of this system, we measured UV–vis spectra of Target-12/hemin, before and after strand displacement (Figure S26). Both spectra exhibited a peak at 398 nm along with a shoulder at 370 nm, indicating the coexistence of monomeric hemin and μ-oxo bihemin (the dimer of hemin). , Of note, after multiple cycles of the strand displacement reactions, the spectra remained similar. We then investigated the UV–vis spectra in the presence of K 10 , which also exhibited the peak at 398 nm and shoulder at 370 nm (Figure S27).…”
Section: Resultsmentioning
confidence: 90%
“…The morphology of aggregate for self-assembled polypeptide is subject to its preparation conditions such as concentration and self-assembling time. , The peptide molecules with a sequence of lipoic acid-GSGS­FGHI­HEGY­EGGK-Fc (P 16 Fc) in aqueous solution at a low initial concentration of 0.1 μM are self-assembled into an irregular nanostructure as shown in Figure A. As the initial concentration of P 16 Fc is increased, the structural appearance is gradually changed from irregular to regular and nanosphere-like with increasing diameters, to be specific, at 1.0 μM with a diameter of approximately 70 nm (Figure B), and at 10.0 μM with a diameter of approximately 400 nm (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the nanospheres were employed for the detection of various disease-related biomarkers through the cooperative coupling of enzymatic reactions. Metalloporphyrins, such as iron(III) protoporphyrin IX (heme), exhibiting enzyme-like catalytic properties, are involved in various biological catalytic processes [258]. Recently, self-assembled nanostructures based on porphyrin derivatives have gained attention due to their remarkable photonic, catalytic, electronic, and biochemical properties, finding applications in diverse fields ranging from catalysis to biosensing [259][260][261].…”
Section: Artificial Enzymesmentioning
confidence: 99%
“…Chen et al demonstrated that nanoporphyrin could serve as a peroxidase-like catalyst for the colorimetric detection of glucose and H2O2 (Figure 15) [262]. In their study, dodecyl trimethyl ammonium bromide (DTAB) was employed as a surfactant to stabilize the suspension of self-assembled zinc tetrakis(4-pyridinyl) porphyrin (ZnTPyP) Metalloporphyrins, such as iron(III) protoporphyrin IX (heme), exhibiting enzyme-like catalytic properties, are involved in various biological catalytic processes [258]. Recently, self-assembled nanostructures based on porphyrin derivatives have gained attention due to their remarkable photonic, catalytic, electronic, and biochemical properties, finding applications in diverse fields ranging from catalysis to biosensing [259][260][261].…”
Section: Artificial Enzymesmentioning
confidence: 99%